Fatigue crack growth in additive manufactured products (Fracture and Structural Integrity, 2015)
Additive Manufacturing (AM) is a new innovative technique that allows the direct fabrication of complex, individual, delicate and high-strength products, based on their 3D data. Selective Laser Melting (SLM) is one of the AM processes that generates metallic components layer by layer using powder-bed technique. The irradiation and consequent melting of metallic powder is realised by the laser source. Employing SLM, especiallycomplex and individual products, such as implants or aerospace parts, are well suited for economic productionin small batches.The first important issue in this work was to analyse the fatigue crack growth (FCG) in titanium alloy Ti-6-4 andstainless steel 316L processed by SLM. As a first step, stress intensity range decreasing tests were performed onSLM samples in their “as-built” condition. The next step was to adopt measures for optimisation of fatiguecrack growth performance of SLM parts. For this purpose various heat treatments such as stress relief  annealing and hot isostatic pressing (HIP) were applied to the CT specimens. Finally, the strong impact of heat treatment on the residual lifetime was demonstrated by numerical fatigue crack growth simulations. For this purpose, the hip joint implant consisting of Ti-6-4 and processed by SLM was taken into account.It was found that residual stresses have a strong influence on the crack growth in Ti-6-4, while the influence ofthe micro-pores on the threshold values remains low. In contrast the results for 316L show that its  fracture mechanical behaviour is not affected by residual stresses, whereas the microstructural features lead tomodification in the da/dN-?K-data. The second fundamental aim of this work was to demonstrate the possibilities of the SLM process. For that reason, the individually tailored bicycle crank was optimised regarding its weight and local stresses and finally manufactured using the SLM system. The iterative optimisation procedure was based on static and cyclic loading situations as well as displacements obtained by results from numerical analyses.
Keywords: Selective Laser Melting